Perianal human tail with lower imperforate anus: A case report - Satoshi Yokoyama; Akinori Sekioka; Hirofumi Utsunomiya (Wolters Kluwer Medknow Publications, 2023)
The human tail is usually attached to the sacrococcygeal skin. However, few reports of the human tail at the perineal or perianal region have been described. Moreover, the tails are rarely accompanied with anorectal malformations (ARMs). Although the exact relationship between the human tail at the perineal or perianal region and ARM remains obscure, we consider that the human tail at the sacrococcygeal region and the perineal or perianal region may have a slightly different mechanism of development.